Improving Communication with Patients Discharged from the Emergency Department with Noncardiac Chest Pain: A Scoping Review with Narrative Synthesis - Ramzi Shawahna; Aya Ghoul; Najlaa Zaid; Wassan Damrah; Mohammad Jaber (Emergency Medicine International)
Background. This scoping review with narrative synthesis aimed to analyze scholarly peer-reviewed articles reporting on improving communication with patients discharged from the emergency department with noncardiac chest pain and qualitatively narrate on and summarize items that can be used in guiding communication with patients discharged from the emergency department with noncardiac chest pain. Methods. The databases of EMBASE/PubMed, Scopus, COCHRANE, CInAHL/EBESCO, UW libraries, and Google Scholar were searched using relevant MeSH and key terms up to February 06, 2020. The selected articles were analyzed for their contents. Items guiding discharge communication were summarized qualitatively. Results. Twenty-five articles were eligible for full review. These were published in between 1994 and 2020. Of those, 16 (64.0%) originated from the United States and 4 (16%) used some interventional design. A total of 45 different items that could be used in guiding discharge communication with patients presenting to the emergency department with chest pain were identified from the studies included in this review. Items were grouped under 6 categories that were related to initial assessment (8 items), information on diagnosis (7 items), information on discharge (9 items), follow-up suggestions (7 items), symptoms that promote return to the emergency department (7 items), and treatment plan (7 items). Conclusion. Communication with patients discharged from the emergency department with noncardiac chest pain can be improved. Results of this investigation might be helpful in guiding quality improvement projects aimed for further improvement of communication with patients discharged from the emergency department with noncardiac chest pain.